OPTIMASI ALGORITMA NEURAL NETWORK DENGAN ALGORITMA GENETIKA DAN PARTICLE SWARM OPTIMIZATION UNTUK MEMPREDIKSI HASIL PEMILUKADA - Badrul, Mohammad (LPPM Universitas Nusa Mandiri, 2017)
Indonesia has one of the islands spread from Sabang to Merauke. State of Indonesia which consists of several islands gave birth to awide variety of ethnic and cultural diversity. State of Indonesia which consists of several islands divided into 34 provinces. Indonesia is one countrythat adheres to the democratic system in the world. to achieve this goal, one of which is seen at the democratic party to choose the future leaderswho will represent the people in parliament. Elections were held in Indonesia is to choose the heads of both the president and vice president,members of Parliament, Parliament and Council. Research relating to the election had been conducted by researchers is using decision treemethod or by using a neural network. The method used was limited without doing optimization method for the algorithm. In this study, researchers will conduct research focusing on the optimization using genetic algorithm optimization and particle swarm optimization with the aid of neural network algorithms. After testing the two models of neural network algorithms and genetic algorithms are the results obtained by the neural network algorithm ptimization particle swarm optimization algoritmasi accuracy value amounted to 98.85% and the AUC value of 0.996. While the neural network algorithm with genetic algorithm optimization accuracy values of 93.03% and AUC value of 0.971